The dynamic coastal landscape of Crete between the 7th and early 9th century AD - Roussos, Konstantinos (My University, 2024)
This paper intends to shed light on the changes that occurred in the coastal landscape of Crete during the period of Transformations (7th - 9th centuries AD) with a special focus on ports and harbors. It discusses how these changes reflect the changing social, economic and political conditions in the Aegean Archipelago between the mid-7th and early 9th centuries AD. It tests questions concerning how ports and harbors interacted with one another, with fortified sites, with other places across water, and with maritime navigation. Overall, considering recent historical and archaeological evidence, it aims to shed more light on the period of Transformations, highlighting certain aspects of the resilience and adaptability of the insular communities of Crete. Ports and harbors are not regarded as isolated dots on a map, but instead, they are viewed as parts of various networks with different types of interaction and as cultural products of political, social and economic circumstances. This human-centered approach puts at the center of attention people, their actions and experiences, as well as their engagement with natural environment. Maritime mobility and interaction are considered as key factors of island life. Due to the complexity of the topic, this research adopts an interdisciplinary framework which includes historical and archaeological approaches, combined with spatial analytical tools offered by the Digital Humanities (Geographical Information Systems).
Keywords: Crete; Aegean Sea; Byzantine Ports and harbors; Landscape Archaeology; GIS; period of Transformations